A Review of Cases of Fraud Committed in the Sphere of Equity Participation in the Construction of Residential Real Estate in the Republic of Kazakhstan - ZHUNISBEKOV, Nurken Nurakhmetovich (Journal of Advanced Research in Law and Economics, 2018)
The purpose of this article is to conduct a comprehensive scientific analysis of social conditioning, the criminal legal nature, criminological characteristics, theoretical and practical approaches to investigating crimes committed in the sphere of shared housing construction and to develop on their basis the recommendations aimed at increasing the efficiency of the activities of internal affairs agencies. This article describes the current state of law enforcement practice of crimes in the sphere of equity participation in the construction of residential facilities in the Republic of Kazakhstan. As for the subject of research, there are a number of problems related to the qualification and definition of jurisdiction in cases of fraud with shared construction of residential facilities. This article touches upon cases of fraud committed in the mentioned social sphere, which has spread widely in the Republic of Kazakhstan and is classified as a category of difficultly provable criminal offenses. The analysis of law enforcement practice has shown that the misconduct of relevant state bodies, their erroneous actions often significantly predetermine the negative outcome of such social phenomenon as equity participation in the construction of residential real estate. The acquisition and alienation of residential real estate is an important and responsible period in the life of each person, since real estate is often the only vital value for many people. The high cost of real estate and its invaluable social significance cause the emergence of various kinds of intermediaries and criminal structures around it, the spread of fraud in this sphere, including in the sphere of equity participation in housing construction.